Human Sulfotransferase Assays With PAPS Production in situ - Sun, Yanan; Harps, Lukas Corbinian; Bureik, Matthias; Parr, Maria Kristina (Frontiers in Molecular Biosciences, 2022)
For in vitro investigations on human sulfotransferase (SULT) catalyzed phase II metabolism, the costly cofactor 3'-phosphoadenosine-5'-phosphosulfate (PAPS) is generally needed. In the present study, we developed and optimized a new approach that combines SULT-dependent biotransformation using recombinant and permeabilized fission yeast cells (enzyme bags) with PAPS production in situ applying quality by design principles. In the initial application of the procedure, yeast cells expressing human SULT1A3 were used for the production of 4-hydroxypropranolol-4-O-sulfate from 4-hydroxypropranolol. The optimized protocol was then successfully transferred to other sulfonation reactions catalyzed by SULT2A1, SULT1E1, or SULT1B1. The concomitant degradation of some sulfoconjugates was investigated, and further optimization of the reaction conditions was performed in order to reduce product loss. Also, the production of stable isotope labeled sulfoconjugates was demonstrated utilizing isotopically labelled substrates or [34]S-sulfate. Overall, this new approach results in higher space-time yields while at the same time reducing experimental cost.